Monovacancy–As complexes in proton-irradiated Ge studied by positron lifetime spectroscopy. (15th January 2015) - Elsayed, M.; Yu. Arutyunov, N.; Krause-Rehberg, R.; Emtsev, V.V.; Oganesyan, G.A.; Kozlovski, V.V.
Abstract: We applied positron annihilation lifetime spectroscopy to study the proton-irradiation-induced defects in germanium and its annealing behavior. The n -doped Ge ([As] = 9 × 10 17 cm −3 ) samples were irradiated at room temperature with a proton energy of 15 MeV at a dose of 10 15 cm −2 . We distinguished a complex containing a vacancy and arsenic atoms. In addition, we observed shallow positron traps, which are ascribed to the impurities in a Ge lattice crystal. Isochronal annealing experiments were carried out in the temperature interval 300–820 K. Temperature-dependent positron lifetime measurements were performed after each annealing step. During isochronal annealing of the proton-irradiated Ge, a vacancy–As complex was found to dissociate to its constituents and the single monovacancies eventually anneal out. Two annealing stages were observed: the first, at ∼450 K, was attributed to the dissociation of complexes and the second annealing stage, at 650 K, was assigned to annealing of vacancies. Shallow positron traps anneal in the temperature range 540–660 K.